La Première Guerre mondiale vue de Paris : de la correspondance d’Étienne de Nalèche, directeur du Journal des Débats, à Pierre Lebaudy, au « journal d’un bourgeois de Paris », 1914-1919 - Odile Gaultier-Voituriez (In Situ)
During the First World War, Étienne de Nalèche, who was the editor in chief of the daily paper, the Journal des Débats remained in Paris. Between 1914 and 1919, every day, he penned a letter to his friend Pierre Lebaudy, member of a wealthy family of industrialists involved in sugar production. Despite his advanced years, Lebaudy had managed to be enrolled as an officer. In our article, the context and circumstances of the production of these letters is first presented. We then go on to analyse the corpus of 1,020 letters in all, from one to four pages long, with a structured contents. We examine too how this collection was conserved by the Nalèche family, how several historians have all commented on its remarkable interest and how it ended up in the possession of the Fondation nationale des sciences politiques in Paris (Sciences Po). The originality of the collection lies in the evolution of its status, from a well-written correspondence between two friends to a chronicle of the war, as seen from Paris. The general, political and diplomatic interest of the letters becomes more important than the personal aspects. An example of a letter dated 16 November 1917 is included with the article, in facsimile and with its transcription.